Pengaruh Temperatur Hardening dengan Media Pendingin Udara terhadap Sifat Mekanik Baut Pengikat Ban Truck (41Cr4) - Yulfitra; M. Z. Haris (CV. IRA PUBLISHING, 2022)
In today's development, metal materials are widely used for various components that can withstand large loads due to their excellent durability and strength. Although composite materials have been found as a substitute for metal, not all machine elements can be replaced with composite materials. as metal functions like bolts. In this case, the bolt failed in the form of a fracture. Therefore it is necessary to research to analyze the failure. This study describes the mechanical properties obtained from the results of bolt testing, which includes tensile testing, hardness testing, and microstructural testing by first being heat treated. The results of the tensile strength test of the specimen for conditions without heat treatment, hardening temperature 850°C, tempering 550°C, and tempering 500°C were 3392.78 MPa, 3478.55 MPa, 3449.95 MPa, and 3402,30 MPa respectively. The hardness values ​​of untreated specimens, hardening 850°C, tempering at 550°C, and tempering at 500°C were 297.4 HRC, 360.8 HRC, 343.2 HRC, and 329.7 HRC. And in testing the microstructure of the influence of air conditioning media and temperature differences, it produces three microstructures ferrite, pearlite, and martensite.